2021
DOI: 10.1002/solr.202100243
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Codoped Nickel Oxide Hole–Transporting Layers for Highly Efficient Inverted Perovskite Solar Cells

Abstract: Inverted perovskite solar cells (PSCs), which feature an attractive structure for diverse applications such as tandem SCs or flexible devices, continue to be rapidly developed. Among various hole‐transporting layer (HTL) materials, nickel oxide (NiO x ) is widely used as a stable and superior HTL even though it exhibits poor conductivity. Although various methods have been proposed to overcome the low conductivity of NiO x films, codoping methods have not been extensively studied and remain poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…A similar observation was made by Yi et al for Li, Cu co-doped NiO x , where the Ni 3+ : Ni 2+ ratio increased from 1.6 (pristine) to 2.8 upon Li : Cu (10 : 0 vol%) doping, which further increased to 3.89 upon Li : Cu (0 : 10 vol%) doping. 26 Yin et al and Chen et al, in their work on K-doped NiO x also reported a similar trend, where the Ni 3+ : Ni 2+ ratio increased from 1.13 to 2.55 and 1.69 to 2.24, respectively. 12,38 This is a clear indication that cation dopants have a pronounced impact on improving the hole density by introducing acceptor-type defects of nickel vacancies.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…A similar observation was made by Yi et al for Li, Cu co-doped NiO x , where the Ni 3+ : Ni 2+ ratio increased from 1.6 (pristine) to 2.8 upon Li : Cu (10 : 0 vol%) doping, which further increased to 3.89 upon Li : Cu (0 : 10 vol%) doping. 26 Yin et al and Chen et al, in their work on K-doped NiO x also reported a similar trend, where the Ni 3+ : Ni 2+ ratio increased from 1.13 to 2.55 and 1.69 to 2.24, respectively. 12,38 This is a clear indication that cation dopants have a pronounced impact on improving the hole density by introducing acceptor-type defects of nickel vacancies.…”
Section: Resultsmentioning
confidence: 59%
“…S8 (ESI †), and the resulting reduction in morphology-induced scattering effect upon doping. 26 This observation was verified further by calculating the weighted average transmittance (% WAT). The WAT plot is shown in Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Specifically, the Ni 3+ /Ni 2+ ratio is enhanced by ≈12.5%, 19.8%, 13.13%, 5.66%, 2.31%, 32.5%, 17.8%, and 18.7% in Cs-doped, [89] Zn-doped, [90,91] Cddoped, [92] Pb-doped, [93] Al-doped, [94,95] K-doped, [96] Fe-doped, [97] and Eu-doped NiO, [98] respectively, whereas it is suppressed by 14.3% in Co-doped NiO. [99] The Ni 3+ /Ni 2+ ratio was reported to increase in Li-Mg, [87] Li-Cu, [100][101][102] Li-Ag, [103] Zn-Ce, [104] Li-Co, [105] and Li-Co-Mg [106] codoped NiO layers compared to the pristine NiO layers, suggesting an increase in the hole conductivity. Therefore, when the Ni 3+ /Ni 2+ ratio is increased, the oxidation of Ni 2+ into Ni 3+ in NiO is also reported to increase, resulting in a high Ni 2+ deficiency and an oxygen-rich nature, which directly contribute to the p-type conductivity of NiO.…”
Section: Elemental Dopingmentioning
confidence: 99%
“…[107] This type of behavior is not observed in doped-NiO when they were used as HTL in inverted perovskite solar cells. Thus, to determine the influence of the doping concentration on increasing the conductivity or hole mobility in doped NiO films, a few reports have presented conductivity measurements [83,87,92,95,97,102] /Hall effect measurements, [80,84,97] which we believe is essential for this complex system.…”
Section: Elemental Dopingmentioning
confidence: 99%